Ribulose-1,5-bisphosphate regeneration in the Calvin-Benson-Bassham cycle: Focus on the last three enzymatic steps that allow the formation of Rubisco substrate - Meloni, Maria; Gurrieri, Libero; Fermani, Simona; Velie, Lauren; Sparla, Francesca; Crozet, Pierre; Henri, Julien; Zaffagnini, Mirko (Frontiers in Plant Science, 2023)
The Calvin-Benson-Bassham (CBB) cycle comprises the metabolic phase of photosynthesis and is responsible for carbon fixation and the production of sugar phosphates. The first step of the cycle involves the enzyme ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco) which catalyzes the incorporation of inorganic carbon into 3-phosphoglyceric acid (3PGA). The following steps include ten enzymes that catalyze the regeneration of ribulose-1,5-bisphosphate (RuBP), the substrate of Rubisco. While it is well established that Rubisco activity acts as a limiting step of the cycle, recent modeling studies and experimental evidence have shown that the efficiency of the pathway is also impacted by the regeneration of the Rubisco substrate itself. In this work, we review the current understanding of the structural and catalytic features of the photosynthetic enzymes that catalyze the last three steps of the regeneration phase, namely ribose-5-phosphate isomerase (RPI), ribulose-5-phosphate epimerase (RPE), and phosphoribulokinase (PRK). In addition, the redox- and metabolic-based regulatory mechanisms targeting the three enzymes are also discussed. Overall, this review highlights the importance of understudied steps in the CBB cycle and provides direction for future research aimed at improving plant productivity.